Three Cases of Organized Hematoma of the Maxillary Sinus: Clinical Features and Immunohistological Studies for Vascular Endothelial Growth Factor and Vascular Endothelial Growth Factor Receptor 2 Expressions - Shoichiro Imayoshi; Takeharu Kanazawa; Noriyoshi Fukushima; Hisashi Kikuchi; Masayo Hasegawa; Takafumi Nagatomo; Hiroshi Nishino (Case Reports in Otolaryngology)
Objectives. Organized hematoma (OH) is a rare, nonneoplastic, hemorrhagic lesion causing mucosal swelling and bone thinning, mainly in the maxillary sinus. We aimed to clarify the clinical presentation and treatment of OH. Methods. Three cases of maxillary sinus OH and a literature review are presented. Results. Three men aged 16–40 years complained of nasal obstruction, frequent epistaxis, and/or headache. Clinical and radiological examinations revealed a maxillary sinus OH. They were cured in a piecemeal fashion via endoscopic middle meatal antrostomy. Furthermore, vascular endothelial growth factor and its receptor were expressed in the lesion. Conclusions. The pathogenesis of OH is unclear and it presents various histological and imaging findings; however, it is not difficult to rule out malignant tumors. Minimally invasive surgery such as endoscopic sinus surgery can cure it completely. Thus, it is important to determine the diagnosis using CT and MRI and to quickly provide surgical treatment.